Evidence of Hydrocarbon Generation and Overpressure Development in an Unconventional Reservoir Using Fluid Inclusion and Stable Isotope Analysis From the Early Triassic, Western Canadian Sedimentary Basin - Kingston, Andrew; Ardakani, Omid H.; Watt, Elizabeth; Samson, Iain M. (Frontiers in Earth Science, 2022)
Deep burial of sedimentary basins results in the development of complex diagenetic environments influenced by pressure, temperature, and metasomatic chemical processes. Fracture systems resulting from deep tectonic-related burial can provide archives of physio-chemical characteristics during burial helping unravel diagenetic events such as hydrocarbon migration and paleobarometry. The Early Triassic Montney Formation in the Western Canadian Sedimentary Basin is a highly productive unconventional hydrocarbon reservoir that has undergone multiple phases of tectonic-related burial and uplift resulting in the formation of a series of calcite-filled fracture systems. These fracture systems occur as vertical to sub-vertical fractures, brecciated zones, and horizontal bedding-plane parallel fractures that are rich in co-occurring, but not co-genetic aqueous and petroleum fluid inclusion assemblages. Fluid inclusion microthermometry, Raman spectroscopy, and stable isotope analysis of these fracture systems and host rock reveals paleobarometric and temperature conditions during fracture formation. Vertical fractures formed at temperatures exceeding 142°C during peak burial associated with the Laramide orogeny ~50Ma. Similarities in modeled oxygen isotope values of calcite parent fluids and pore water implicate locally sourced carbonate in fracture calcite. Therefore, low permeability and closed system-like conditions were prevalent throughout initial fracture formation and cementation. Petrographic analysis of brecciated and horizontal fractures show evidence of hydrocarbon generation and migration into fracture-filling calcite. Modeling of petroleum inclusion paleobarometry indicates entrapment pressures approaching or even exceeding lithostatic pressure consistent with the development of overpressure associated with the thermal maturation of organic matter following peak burial. Combined use of aqueous and petroleum fluid inclusions in this deeply buried sedimentary system offers a powerful tool for better understanding diagenetic fluid flow, the timing of hydrocarbon migration/maturation, and helps constrain the pressure-temperature history important for characterizing economically important geologic formations.